2005
DOI: 10.1038/sj.jhh.1001819
|View full text |Cite
|
Sign up to set email alerts
|

Markers of collagen synthesis is related to blood pressure and vascular hypertrophy: a LIFE substudy

Abstract: Cardiac fibrosis and high levels of circulating collagen markers has been associated with left ventricular (LV) hypertrophy. However, the relationship to vascular hypertrophy and blood pressure (BP) load is unclear. In 204 patients with essential hypertension and electrocardiographic LV hypertrophy, we measured sitting BP, serum collagen type I carboxy-terminal telopeptide (ICTP) reflecting degradation, procollagen type I carboxy-terminal propeptide (PICP) reflecting synthesis and LV mass by echocardiography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Apart from 1 report detailing elevated plasma levels of CITP in subjects with untreated hypertensive compared with normotensive subjects, 16 most clinical studies associate hypertension with diminished CITP and MMP activity [17][18][19] and greater vessel type I collagen content. 20 Nonetheless, based on the in vivo results presented here and our previous ex vivo findings, 3 it appears that MMPs are induced within days of the onset of hypertensive conditions and participate in collagen breakdown, increasing vessel distensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from 1 report detailing elevated plasma levels of CITP in subjects with untreated hypertensive compared with normotensive subjects, 16 most clinical studies associate hypertension with diminished CITP and MMP activity [17][18][19] and greater vessel type I collagen content. 20 Nonetheless, based on the in vivo results presented here and our previous ex vivo findings, 3 it appears that MMPs are induced within days of the onset of hypertensive conditions and participate in collagen breakdown, increasing vessel distensibility.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure other markers of collagen synthesis (type I carboxy-terminal pro-collagen peptide) or degradation (type I collagen carboxy-terminal telopeptide) that may have been related to echocardiographic measures. 43,44 Additionally, we did not assess genetic factors, which may have explained some of the variation in PIIINP levels. Lastly, transmitral and tissue Doppler measurements were not available at this examination.…”
Section: Study Limitationsmentioning
confidence: 99%
“…17 However, several studies have shown that serum markers of collagen turnover are useful in the diagnosis of myocardial fibrosis, especially serum procollagen type I propeptide (PIP), which is significantly higher in hypertensive patients with LVH than in normotensive controls. [18][19][20] It also correlates with collagen volume fraction (CVF) on endomyocardial biopsies and decreases in parallel with its regression during antihypertensive treatment. 19,21 Moreover, transforming growth factor (TGF)-β1 is known to play an important role in myocardial fibrosis by stimulating the synthesis of matrix molecules in hypertensive heart disease.…”
mentioning
confidence: 99%
“…In the present study, we compared target organ status, such as LVH, parameters of LV diastolic function, and biochemical markers of myocardial fibrosis (concentrations of TGF-β1 and PIP) [17][18][19][20][21][22][23][24][25]27 in individuals with NT, WCH, and EH. We also ascertained the correlation between the biochemical markers of myocardial fibrosis and indices of LV diastolic function in patients with WCH.…”
mentioning
confidence: 99%